Wall-Diaphragm Connection Assessment Guidelines for URM Buildings. - Abdul Razak, Abdul Karim; Quenneville, Pierre; Norazzlina, M.Sa'don; Ingham, Jason M. (2011)
The connections between walls and diaphragm in unreinforced masonry (URM) buildings typically consist of two major parts. The first part is the wall anchorages and the second part is the diaphragm connections. From the NZNSEE (1995) and FEMA (2006) guidelines, the connection strength values given by both guidelines are apparently related only with the possible failures of the masonry wall anchorages, and no procedures are currently available to identify the strength values related to failure of the timber bolted connections. This latter failure mode is important to consider as the minimum strength value that will govern the wall-diaphragm connection capacity can be acquired from the diaphragm connections. To counter this limitation, this study recommends a set of design equations to assess the strength of the timber bolted connections. By using these equations, in addition to the default connection strength values provided by the guidelines, the expected strength level of wall-diaphragm connections can be accurately assessed.